Celecoxib promotes degranulation of CD8(+) T cells in HPV-induced lesions of K14-HPV16 transgenic mice - Carlos Santos (2016)
Aims: Human papillomavirus (HPV) is a known biologic carcinogen which is commonly transmitted through sexual intercourse. CD8(+) T cells are known effectors against tumour cells and an important prognostic marker in HPV-induced cancers. COX-2 inhibitors enhance CD8(+) T cell activity against some cancers. In this work, we sought to study the presence and activation of CD8(+) T lymphocytes in lesions from K14-HPV16 transgenic mice and the immunomodulatory effect of celecoxib (CXB) over these cells. Main methods: Skin samples of CXB-treated and untreated HPV16(-/-) and HPV16(+/-) mice were enzymatically digested and analysed by flow cytometry to assess CD8+ and CD8(+) CD107a(+) T cell infiltrates. Matched skin samples were classified histologically. Key findings: HPV16(+/-) mice presented higher CD8(+) T cell infiltration than HPV16(-/-) animals (P < 0.001). Older HPV16(+/-) animals showed epidermal dysplasia and increased percentages of CD8+ CD107a(+) T cells compared with younger animals with hyperplasia (P < 0.001), validating this model for testing the effects of celecoxib on CD8(+) T cells. CXB-treated HPV16(+/-) mice showed higher percentages of CD8(+) CD107a(+) T cells compared with untreated HPV16(+/-) animals (P < 0.01), but no differences were observed concerning the progression of epidermal lesions. Significance: These findings indicate that celecoxib enhances the degranulation of CD8(+) T cells on HPV16-induced lesions, suggesting the potential clinical use of COX-2 inhibitors. Additionally, this study demonstrates the usefulness of the K14-HPV16 mouse model for testing therapeutic immunomodulatory approaches.